Visions of the Possible: Towards a Signature Pedagogy for Information Literacy Instruction - Arteaga, Roberto (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2023)
In academic libraries, library instruction often takes the form of one-shot instruction and is not always deeply linked to the broader curricula. This article will argue that if library instruction in an academic setting is to be perceived as beneficial to student learning, it needs to coalesce around a set of specific values and teaching practices. To do so, this article will build on scholarship about signature pedagogies to continue the work of identifying a signature pedagogy for academic libraries engaged in information literacy instruction. To Lee S. Shulman, signature pedagogies outline the teaching practices used to educate new professionals, and they are essential to understanding how a profession develops. By participating in the process of developing a signature pedagogy, academic librarians would be able to engage in questions about the nature and purpose of their work, as well as set a foundation for how practicing and developing library professionals are educated and continue to be educated.